Efektivitas Strategi Story Selling di Instagram untuk Meningkatkan Penjualan Sayur Organik Merbabu (SOM) - Nuzuli, Ahmad Khairul; Raya, Alia Bihrajihant (Avant Garde, 2024)
This study aims to explore the effectiveness of the story selling communication strategy on Instagram in increasing sales of Sayur Organik Merbabu (SOM). The results of this study indicate that the story selling strategy on Instagram is effective in increasing SOM sales. By exploring the emotional connection between consumers and products, stories about local farmers, organic farming methods, and commitment to environmental sustainability have succeeded in building a strong and authentic brand image. Consumers feel more connected to this product because they see and understand the natural and environmentally friendly behind-the-scenes process. Transparency in the production process is key to increasing consumer trust in SOM products. By honestly showing how vegetables are grown, harvested, and processed without chemicals. In this case, education about the benefits of organic vegetables also plays an important role in building consumer awareness and trust. In addition, the use of attractive and high-quality visuals, such as images and videos, as well as the use of Instagram features such as stories, reels, and IGTV, help convey stories dynamically and interactively. The use of relevant hashtags and collaboration with influencers have also proven effective in increasing the visibility of SOM accounts on Instagram. In conclusion, this study shows that the story selling strategy on Instagram is not only an effective marketing tool to increase sales, but also a means to build stronger and more sustainable relationships with consumers. This study provides valuable insights for organic vegetable businesses to adopt a similar approach in their digital marketing strategies, as well as to utilize social media more effectively to build brand awareness and consumer trust in the future.